(untitled) (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2023)
In many discourses, Eugene Achike in Chimamanda Adichie’s Purple Hibiscus has been blamed for his high handedness and the ensuing misfortunes that befell his family. However, no view has actually considered Eugene as a victim; therefore, the narrative regarding his character has been lopsided. This paper therefore, utilizing the content analysis methodology, contends that Eugene is a patient of a mental health disorder that makes him a casualty as well in the saga concerning his family. The paper advocates for an unrelenting effort towards the awareness-raising campaigns for various types of mental health challenges. It is equally hoped that through this work, people will learn not to be too quick in judging others.